ANALYSIS OF FLUVIAL LANDFORMS IN VEL RIVER BASIN (International Journal of Food and Nutritional Sciences, 2022)
The geological works of fluvial processes or rivers are called three- phase work comprisingerosion, transportation and deposition. The fluvial landforms are divided into two major groups. These areErosional landforms and Depositional landforms. Erosional and depositional landforms in Vel River Basinare studied in the present paper. The significance of this study is to understand the geologicalcharacteristics and fluvial landforms in the Vel Basin.